Wheel and Shoe Composite Stair Climbing Wheelchairs and Dynamic Analysis of Wheel Shoe Switching - Zhu Hua; Ge Haiwen (Jixie chuandong)
In response to the current issues of wheel and shoe composite ladder wheelchairs, such as tire interference with the track, and collision between the wheelchair and the top platform during ladder climbing, a wheel shoe composite stair climbing wheelchair with a swing arm track chassis as the stair climbing mechanism and a new wheel shoe switching scheme is designed. Its mathematical model is established, the centroid coordinates, the vertical displacement curve of the center of mass for climbing stairs are analyzed, and the dynamic change curve of the swing arm motor and electric push rod during the four stages of wheel shoe switching are obtained. The up and down stairs mode and the wheel shoe switching mode of a wheelchair are simulated in RecurDyn software. The simulation results indicate that the wheelchair is smooth and safe during the process of ascending and descending stairs, and the theoretical values of the dynamics of the four stages of wheel shoe switching are consistent with the simulation situation. The research provides a theoretical basis for the mechanical structure design, electric push rod selection, and swing arm motor selection of this type of ladder wheelchairs.